Comparative evaluation of the tympanic membrane perforations recovery, depending localization - S. N. Kocherov (Бюллетень сибирской медицины)
The aim of the study was to evaluate the efficiency tympanic membrane traumatic defect silicone disc shielding in combination with endaural laser therapy depending on the defect location.Materials and methods. The paper analyzes the results of treatment of 50 patients. The first group (25 people) – had a defect in frontal quadrant, the second group (25 people) – in rear forated silicone disk and endaural laser therapy. Each patient received six three-minute radiation sessions. A single biological dose was 50 J/cm2, the total of 300 J/cm2. Results and discussion. Tympanic membrane defect area was evaluated in each group in dynamics. In the first group before the start of treatment, the average perforations area was (14,2 ± 0,93) mm2, and in the second group (18,6 ± 2,31) mm2. After three months of first group observation in 2 (8%) patients tympanic membrane remained defective and the average area was (3,4 ± 071) mm2. The second group the perforation observed in 1 (4%) patient and average area was (2,8 ± 0,63) mm2 area. The differences in groups were considered statistically significant. The average duration of restoration tympanic membrane integrity in first group was (16 ± 5) days, the second group (11 ± 3) days. The differences in groups were considered statistically significant (t = –3,3; p = 0,003).Conclusion. Thus, posterior quadrants tympanic membrane traumatic perforations demonstrated more favorable prognosis in terms of convalescence.